2009
DOI: 10.1144/sp315.12
|View full text |Cite
|
Sign up to set email alerts
|

Basilochelys macrobios n. gen. and n. sp., a large cryptodiran turtle from the Phu Kradung Formation (latest Jurassic-earliest Cretaceous) of the Khorat Plateau, NE Thailand

Abstract: A large cryptodiran turtle, Basilochelys macrobios n. gen. n. sp. is described from the latest Jurassic–earliest Cretaceous Phu Kradung Formation of NE Thailand, on the basis of skull, shell and other postcranial elements. Basilochelys presents a combination of primitive and derived characters. The derived characters include sculptured skull roof and shell surface; deeply embedded canalis caroticus internus; foramen posterius canalis carotici interni completely surrounded by pterygoid; neural formula of 6>4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 26 publications
1
41
2
Order By: Relevance
“…According to the results presented above, this can be interpreted as a variable extent of the ossification of the parasphenoid ventral to the basisphenoid. The recently described Basilochelys macrobios (Tong et al 2009) shows that this variability still exists in early crown-group cryptodires. The evolution of the internal carotid system in fossil eucryptodires is still poorly understood and requires more detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results presented above, this can be interpreted as a variable extent of the ossification of the parasphenoid ventral to the basisphenoid. The recently described Basilochelys macrobios (Tong et al 2009) shows that this variability still exists in early crown-group cryptodires. The evolution of the internal carotid system in fossil eucryptodires is still poorly understood and requires more detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, chelydrids (i.e., snapping turtles) were recognized to have close relationships with kinosternoids (i.e., mud and musk turtles), mostly based on characters derived from the shell, such as the presence of costiform processes and a cruciform plastron (e.g., Gray 1869;Boulenger 1889;Baur 1893;Siebenrock 1909;Williams 1950;Romer 1956;Kuhn 1964;Sukhanov 1964;Ml ⁄ ynarski 1976;Carroll 1988), but early classifications often failed to include important taxa in this grouping, particularly the Central American river turtle Dermatemys mawii Gray, 1847, or wrongfully included others, such as the aberrant Asian big-headed turtle Platysternon megacephalum Gray, 1831. With the advent of cladistic methods, Gaffney (1975aGaffney ( , 1975b suggested that cranial characters link chelydrids with testudinoid turtles and that Platysternon megacephalum should be regarded as a true snapping turtle. Subsequent cladistic analyses supported the distinct nature of pan-chelydrids and placed this clade as sister either to all other extant cryptodires (e.g., Gaffney et al 1991;Hirayama et al 2000;Tong et al 2009) or to testudinoids and trionychoids (e.g., Brinkman and Wu 1999;Joyce 2007). A series of increasingly well-sampled analyses that utilize molecular data (e.g., Shaffer et al 1997;Krenz et al 2005;Parham et al 2006;Barley et al 2010;Crawford et al 2015), however, have more recently revived the sister group relationship between chelydrids and kinosternoids to the exclusion of P. megacephalum.…”
Section: Introductionmentioning
confidence: 85%
“…The shark teeth were recovered from a reddish siltstone level with sandy to microconglomeratic lenses, which was surface collected. The site has yielded a large fossil turtle as well as a theropod tibia Tong et al 2009b). Fragments of hybodont finspines as well as teeth of actinopterygians, crocodiles and theropod dinosaurs were also recovered.…”
Section: Geological Settingmentioning
confidence: 99%